Aplicación del proceso de atención de enfermería en paciente gestante con 20 semanas de embarazo con anemia ferropenia” - Morante Mosquera, Karen Estefania (2019)
The present case is a 24-year-old patient with 20 weeks of gestation who goes to the present house of health entering the emergency service accompanied by her husband with a clinical picture of syncope with evolution of 4 hours, including vertigo, asthenia, arrhythmia, headache, pallor, intolerance to activity and malaise. In addition to pale skin and mucous membranes, weak breaths, absence of edema and bruises. Laboratory tests are performed with red blood cell results under normal levels 3'900,000 mmc and hemoglobin 9gr / dc. Nursing assessment is carried out, the patient and her partner are interrogated, and who do not report personal pathological background or family history. On examination the patient is oriented in space time and person with a Glasgow of 14/15. White skin, pale skin and skin Presents blood pressure of 100/60 mmHg, heart rate 100x' respiratory rate 16x' and a saturation of 95%. A cardiac scan shows arrhythmia to simple observation a very marked pallor Absence of edema and bruises. The diagnosis of nursing with nutritional imbalance is identified: lower than the body needs m / p intake lower than the recommended daily amounts, mucous pallor, r / c, insufficient daily intake. Intolerance to m / p activity, arrhythmia, generalized weakness, fatigue, r/c imbalance between intake and oxygen demand Risk of alteration of the maternal / fetal dyad, manifested by compromise of fetal oxygen transport (due to anemia) Nursing care is provided with favorable results that help improve the patient's health condition.